Di-vision - Jordi Jaria-Manzano (Oñati Socio-Legal Series)
The current geological transition implies the necessity of a paradigm shift in dominant social practices to cope with an emerging unstable global socio-ecological complex, which is being shaped by comprehensive, irreversible and uncertain human agency. Along with sustainability, issues of justice are crucial in this context including climate justice, which addresses the most notorious phenomenon of the transition to the Anthropocene, i.e. climate change. Such a paradigm shift implies the need to go beyond established practices in research and exploring new narratives. This paper develops a possible narrative of the civilizational patterns that led to the human transformation of the planet, and shows the limits of business-as-usual responses to confronting the global crisis brought about by the geological transition, and consequently their limited ability to achieve sustainability and justice in the Anthropocene. The narrative deployed here highlights the centrality of a particular form of vision in Modernity and its contribution to the establishment of hierarchies through the di-vision between the in-di-vidual and the external world, i.e. nature, which is untenable in the Anthropocene.